Inherent versus configurational features - Kortlandt, Frederik (Baltistica, 2019)
There is no example of phonological loss of a High tone on the basis of its position in a word form (as opposed to tonal shift and syntactically conditioned loss). The typological parallels adduced by Olander are all instances of doubly accented word forms resulting from the rise of a new High tone. The new High tone on an initial syllable can be attributed to contact with languages that have initial stress.